Postpartum depression screening in the Neonatal Intensive Care Unit: program development, implementation, and lessons learned - Cherry AS; Blucker RT; Thornberry TS; Hetherington C; McCaffree MA; Gillaspy SR (Journal of Multidisciplinary Healthcare, 2016)
Amanda S Cherry,1 Ryan T Blucker,1 Timothy S Thornberry,2 Carla Hetherington,3 Mary Anne McCaffree,3 Stephen R Gillaspy1 1Department of Pediatrics, Section of General and Community Pediatrics, University of Oklahoma Health Sciences Center, Oklahoma City, OK, 2Department of Psychology, Morehead State University, Morehead, KY, 3Department of Pediatrics, College of Medicine, University of Oklahoma, Oklahoma City, OK, USA Objective: The aims of this project were to describe the development of a postpartum depression screening program for mothers of infants in the Neonatal Intensive Care Unit and assess the implementation of the screening program. Methods: Screening began at 14 days postpartum and was implemented as part of routine medical care. A nurse coordinator facilitated communication with mothers for increasing screen completion, review of critical self-harm items, and making mental health referrals. During the 18-month study period, 385 out of 793 eligible mothers completed the screen. Results: Approximately 36% of mothers had a positive screen that resulted in a mental health referral and an additional 30% of mothers had screening results indicating significant symptoms. Conclusion: Several barriers were identified, leading to adjustments in the screening process, and ultimately recommendations for future screening programs and research. Development of a postpartum depression screening process in the Neonatal Intensive Care Unit involves support, training, implementation, and coordination from administrators, medical staff, new mothers, and mental health specialists. Several predictable challenges to program development require ongoing assessment and response to these challenges. Relevance: This study highlights the expanding role of the psychologist and behavioral health providers in health care to intervene as early as possible in the life of a child and family with medical complications through multidisciplinary program development and implementation, as well as key considerations for institutions initiating such a program. Keywords: NICU, parental stress, barriers, postpartum depression, universal screening, pre term infants